2003
DOI: 10.4049/jimmunol.170.8.4148
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Enterotoxin H Induces Vα-Specific Expansion of T Cells

Abstract: Staphylococcal enterotoxin H (SEH) is a bacterial superantigen secreted by Staphylococcus aureus. Superantigens are presented on the MHC class II and activate large amounts of T cells by cross-linking APC and T cells. In this study, RT-PCR was used to show that SEH stimulates human T cells via the Vα domain of TCR, in particular Vα10 (TRAV27), while no TCR Vβ-specific expansion was seen. This is in sharp contrast to all other studied bacterial superantigens, which are highly specific for TCR Vβ. It was further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 57 publications
(62 reference statements)
1
55
0
Order By: Relevance
“…This is the first time that structural studies showing that a SAg from S. aureus predominantly binds to the TCRVα domain. In line with this structural result, the biological functions of SEH have earlier been studied in biochemical as well as cell-based assays, and both studies strongly suggest that SEH binds and activates T cells through the TCRVα domain 23,24 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This is the first time that structural studies showing that a SAg from S. aureus predominantly binds to the TCRVα domain. In line with this structural result, the biological functions of SEH have earlier been studied in biochemical as well as cell-based assays, and both studies strongly suggest that SEH binds and activates T cells through the TCRVα domain 23,24 .…”
Section: Discussionmentioning
confidence: 80%
“…Since then, many studies have confirmed these findings and this was recently reviewed by Fraser and Proft 22 . However, SEH is different as it binds and activates T cells through the TCRVα 23,24 . When comparing the SEH-TCR complex with other SAg-TCR structures that are available in the RCSB Protein Data Bank (SEB, SEC 3 , SEK, SPE-C, SPE-A, TSST-1), it is clear that TRAV27 binds SEH in the opposite direction compared with how TCRVβs recognize SAgs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although studies have shown that some SAGs expand T cells in a Vα-specific manner [52] or bind directly to the TCR Vα domain [53], TCR recognition by SAGs is primarily dictated by SAG-TCR Vβ interactions. The recently expanded database of SAG-TCR Vβ domain crystal structures allows the construction of a paradigm for how SAGs confer specificity and crossreactivity in TCR recognition.…”
Section: Sag-tcr Specificity and Cross-reactivitymentioning
confidence: 99%
“…A classical feature of SAgs is that they interact with the variable region of the TCR ␤-chain, with each SE family member displaying its own unique V␤ profile (11). However, the characterization of SEH has to some extent generated a paradigm shift in the field of SAg biology, because SEH is able to induce specific activation of human T cells dependent on the variable region of the TCR ␣-chain (TRAV) (12). Before this study, some observations identified skewed TRAV repertoires of T cells after SE stimulation, although this was explained by a contact between MHC and TCR, and recently a crystal structure of the Mycoplasma arthritidis mitogen (MAM) in complex with MHC and TCR showed that MAM contacts both the ␣-domain and the ␤-domain of TCR (13,14).…”
mentioning
confidence: 99%